THE EFFECTS OF 3D MODELING ON PLANNING OF MAXILLOFACIAL SURGERY: A Preliminary CBCT STUDY - Mehmet Asım Özer; Anıl Karaman; Pelin Güneri; Hayal Boyacıoğlu; Figen Gökmen; Meltem Özden Yüce; Elif Şener; Ali Canberk Ulusoy (Cumhuriyet Dental Journal, 2022)
Abstract: Objectives: The aim is to evaluate the contribution of 3D modeling data to the planning of the maxillofacial surgery and to determine the indications of 3D modeling. Materials and Methods: In this preliminary study, CBCT images of 2 patients with the Kodak 9000 3D (Kodak Carestream Health, Trophy, France) system were used. The segmentation procedures of the pathologies were performed manually, and was followed by the construction of the 3D models. A questionnaire was prepared by consensus of the research team, including the parameters which are critical in preoperative maxillofacial surgery planning. Five oral and maxillofacial surgeons independently evaluated both the traditional CBCT data and 3D model assisted data under the same viewing conditions. The extent of their decision change was scored using a 2 point Likert scale. Conventional (pre 3D model) versus 3D model assisted data (post 3D model) scores were analyzed. Pair-wise comparisons were completed using Fisher’s exact test (P < 0.05). Kappa was used to measure inter-observer agreement. Results: In both of the evaluation sessions (pre and post 3D model), operation time, defect size and complication risk factors showed the highest variation for both patients. The difference between the decision change proportions for the variables of pre and post 3D model sessions were not statistically significant (p>0.05). Except 2 observers with excellent agreement for both evaluations (p=0.036), the agreement rates were fair without statistical significance. Conclusions: The results confirmed that personalized 3D modeling constructed by CBCT data may lead to changes in surgical treatment planning protocol of complex cases.